Pelaksanaan Evaluasi Pembelajaran Pada Masa Covid-19 di SMP 3 Muhammadiah Medan - Refika Suhaila; Munawarah Munawarah; Naila Sari (Yayasan Rahmat Islamiyah, 2021)
This research generally aims to explore the learning evaluation system in schools and uncover problems experienced during the Covid-19 pandemic. This type of research is an expolarative research conducted by SMP Muhammadiyah 03 Medan. Sources of data obtained from the teacher. The research subjects were 30 respondents using interview and documentation methods. While the main instrument is the researcher who is equipped with interview tools and mobile phones. The form of qualitative data analysis is descriptive. The results of the study showed that the implementation of the evaluation of the learning of moral aqidah subjects during the Covid19 pandemic was less effective and not maximally carried out, both in the cognitive, affective, and psychomotor aspects. Teachers use various WhatsApp applications as the main means of the evaluation process. Meanwhile, the Zoom Meeting application is rarely used by teachers in learning evaluation activities. Keywords: Evaluation, Learning, Covid-19.